Utilization Of Jenggala Natural Attractions As An Outdoor Activity Infrastructure - Ramadhan, Syahrul Dwi; Kusuma, Indra Jati; Heiza, Fuad Noor (Physical Activity Journal (PAJU), 2024)
Outdoor education is an effort to increase children's learning capacity through learning outside of school. To support the achievement of learning outside the classroom, it is necessary to pay attention to the supporting infrastructure for these activities. The aim of this research is to find out how the Jenggala natural tourist attraction is used as infrastructure for learning activities outside the classroom. This research is quantitative descriptive. The research was carried out at the Jenggala natural tourist attraction, with a sample of 32 PJOK teachers in Baturaden sub-district. This research uses an instrument in the form of a questionnaire regarding the use of tourist objects as infrastructure for outdoor activities, with a reliability value of 0.919 as a data collection tool. Data analysis uses quantitative descriptive with the help of SPSS. The results of the research show that the use of Jenggala natural tourist attractions has been carried out well and fulfills the basis for structuring infrastructure for out-of-class activities. Security indicators obtained an average of 82.5% (excellent). The specification indicator for the out-of-class learning environment obtained an average of 80.5% (very good). The standard size indicator obtained an average of 80.7% (very good). The appropriate land contour indicator obtained an average of 75.8% (good). Based on the results of research data analysis, Jenggala natural tourist attractions have been used as infrastructure for out-of-class activities because Jenggala natural tourist attractions have foundations or indicators that support the achievement of out-of-class activities such as safety indicators, specifications for the out-of-class learning environment, standard sizes, and good land contours. in accordance.